2019
DOI: 10.5430/ijhe.v8n5p143
|View full text |Cite
|
Sign up to set email alerts
|

How to Supervise International PhD Students: A Narrative Inquiry Study

Abstract: This narrative inquiry study was undertaken, recruiting 06 successful PhD students in China. The participants were invited and semi-structured interviews were taken one-by-one. The study aimed to explore information about supervisor-supervisee relationship and factors that motivate international PhD students to enhance their research outcomes in a cross-cultural environment. The qualitative data were coded, using QDA miner lite software. After the formation of initial codes, five major categories were emerged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…Los datos se han categorizado a partir de su análisis manual previo y con posterioridad en una segunda ocasión han sido tratados mediante QDA Miner 4.1. Este programa de análisis de datos cualitativos asistido por computadora (CAQDAS) es aconsejable y habitual en la investigación cualitativa en general (Silver, 2015), incluida la de ámbito académico (Hussain y Ali, 2019).…”
Section: Métodounclassified
See 1 more Smart Citation
“…Los datos se han categorizado a partir de su análisis manual previo y con posterioridad en una segunda ocasión han sido tratados mediante QDA Miner 4.1. Este programa de análisis de datos cualitativos asistido por computadora (CAQDAS) es aconsejable y habitual en la investigación cualitativa en general (Silver, 2015), incluida la de ámbito académico (Hussain y Ali, 2019).…”
Section: Métodounclassified
“…La pregunta cerrada con opción múltiple de carácter cuantitativo ha producido unos datos estadísticos representables. A partir de las dos preguntas abiertas, cualitativas, se han obtenido categorías y descriptores utilizando QDA Miner 4.1, un programa reputado dirigido al análisis de datos resultantes de encuestas, entrevistas, etc., que se ha aplicado anteriormente en el ámbito académico (Hussain y Ali, 2019).…”
Section: Análisis De Los Datosunclassified
“…In addition, supervisor support is of benefit for graduate students who can obtain some constructive suggestions from supervisors such as how to publish in peer reviewed journals and how to successfully complete their graduate degree (O"Keeffe, 2020). Moreover, Hussain and Ali (2019) reported that international doctoral students expected close interaction between supervisors and supervisees, constructive feedback, careful guidance and team work to be supported by their supervisors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Elliot and Kobayashi (2019) conducted a qualitative study and highlighted that supervisor support plays an essential role in facilitating international doctoral students" adaptation into the new academic context. Correspondingly, some scholars (Hussain & Ali, 2019;Hussain & Shen, 2019) illustrated that supervisor"s guidance as part of university support helped students cope with academic barriers, resulting in successful academic adaptation of international students in China.…”
Section: Supervisor Supportmentioning
confidence: 99%
“…(6/8) This shows lack of linguistic competence on one's part that may cause language anxiety. Additionally, it also suggests the intercultural communication anxiety due to unequal linguistic competencies of mother tongue and second language and also the one who is higher in rank might cause anxiety among speakers (Hussain & Ali, 2019).…”
Section: Social Status and Self-identitymentioning
confidence: 99%